THE INFLUENCE OF WORLD CPO PRICE ON REAL EXCHANGE RATE OF RUPIAH THROUGH THE CHANGES OF MONEY SUPPLY, INTEREST RATE AND INFLATION - Lubis, Rizky Amelia Zahrah; Ruslan, Dede; Zainal, Andri (Journal of Community Research and Service, 2018)
AbstractThe aim of this research is to anaylse the influence of world CPO price on real exchange rate of Rupiah through the changes of money supply, interest rate, and inflation. This is a quantitative research employing eviews 6.0. This current research hasshown that the influence of world CPO price to real exchange rate of Rupiah through the changes of money supply, interest rate, and inflation in Indonesia between 2008(q1-q4) “ 2015(q1-q4)) is significant and of positive value. Data analysis in this research wasemploying descriptive method, equipped with econometric data analysis with double linier regression analysis model applied by using regression. The simultanous equivalence was done by Two-Stage Square / 2 SLS) model.KeyWords: Real Exchange Rate of Rupiah, World CPO Price, Supply of Money, Interest Rate, Inflation